Wpisany w gwiazde Davida - Linkowski, Grzegorz (Poland : Telewizja Polska, 1997)
A compelling portrait of a man in search of his identity. On his 35th birthday, Father Romuald Jakub Weksler-Waszkinel, learned that he was a Jew saved from the Ghetto of Swieciany as an infant by a Christian woman. Now he must reconcile his Jewish roots with his life as an ordained Priest.
Duration: 00:27:00
Keywords: Documentary films